2022
DOI: 10.1523/jneurosci.2410-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Astrocytic Regulation of Excitation and Inhibition by Stress Exposure and in Severe Psychopathology

Abstract: Dysregulation of excitatory and inhibitory signaling is commonly observed in major psychiatric disorders, including schizophrenia, depression, and bipolar disorder, and is often targeted by psychological and pharmacological treatment methods. The balance of excitation and inhibition is highly sensitive to severe psychological stress, one of the strongest risk factors for psychiatric disorders. The role of astrocytes in regulating excitatory and inhibitory signaling is now widely recognized; however, the specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 140 publications
2
2
0
Order By: Relevance
“…Lateral amygdala-specific reduction of astrocyte GR expression revealed the central role played by astrocytes in mediating the effects of stress hormones on this brain circuit. Indeed, reducing GR expression in astrocytes completely reversed cognitive impairment, an observation that strongly supports the growing literature suggesting astrocytes as therapeutic targets for affective disorders 6365 . The astrocytic impairments induced by ELS, in addition to specific astrocyte disruption (CalEx and dnCx43) that replicate the effect of stress, support the notion that astrocytic modifications are not simply downstream of neuronal dysfunction but rather place astrocytes as key mediators of synaptic and cognitive impairments.…”
Section: Discussionsupporting
confidence: 78%
“…Lateral amygdala-specific reduction of astrocyte GR expression revealed the central role played by astrocytes in mediating the effects of stress hormones on this brain circuit. Indeed, reducing GR expression in astrocytes completely reversed cognitive impairment, an observation that strongly supports the growing literature suggesting astrocytes as therapeutic targets for affective disorders 6365 . The astrocytic impairments induced by ELS, in addition to specific astrocyte disruption (CalEx and dnCx43) that replicate the effect of stress, support the notion that astrocytic modifications are not simply downstream of neuronal dysfunction but rather place astrocytes as key mediators of synaptic and cognitive impairments.…”
Section: Discussionsupporting
confidence: 78%
“…Our findings and previous studies suggest that glutamatergic dysfunction in individuals with PTSD could be due to disrupted glucocorticoid signaling 1 , astrocyte dysfunction 1,68,69 , or increased inflammation 70 . These factors may impair glutamatergic transmission and metabolism in the PFC 1 .…”
Section: Discussionsupporting
confidence: 68%
“…Studies have shown that acute stress and corticosterone administration increased extracellular glutamate in rats 1, 6-8 , whereas chronic stress lowered glutamate 13,14 . The single prolonged stress paradigm also resulted in lower glutamate and glutamine in the rat PFC measured seven days after removing the stressor [10][11][12] , demonstrating that acute stress can have persistent effects on glutamate signaling 69 . Stress negatively impacts astrocytes 1,68 , which are crucial for glutamate clearance and metabolism.…”
Section: Discussionmentioning
confidence: 88%
“…These included for example the cholinergic system in SSD: VAChT was an important predictor in our dominance model. Interestingly, acetylcholine is emerging as a promising new treatment target for both positive and negative symptoms in schizophrenia, as highlighted by a recent phase 3 trial indicating efficacy of the M1 and M4 agonist xanomeline-trospium 88 . M1 was among the most important predictors for CHR-P, but not SSD or CHR-T, phenotypes.…”
Section: Discussionmentioning
confidence: 99%